Punk Muslim: Ekspresi ldentitas Keagamaan Subkultur Muslim Urban - Rahmat Hidayatullah (Kawalu: Journal of Local Culture, 2015)
This paper attempts to understand the expression of Punk Muslim's religious identities as an example of the interration process between religion and modernity, particularly Islam and popular culture in the context of contemporary Muslims' everyday life through the perspectives of cultural and religious studies. According to Lynn Schofield Clark, the study of interraction process between religion and popular culture involves a number of crucial questions: How is religion represented and understood in the landcape of popular culture? How are popular culture aspects adopted by religion as tools to strengthen people's identities? How do certain religious groups use popular culture as a source or a way to reflect and discuss the perspectives and practices of their religious life? How are religious traditions well-transmitted to the youth through stories, pictures, sounds and rituals? Keywords: Punk, Muslims, Religious Identities, Modernity, Popular, Culture